A Color Image Encryption Algorithm Based on Chaotic Map and Discrete Wavelet Transform - Shafique, Arslan; Ahmed, Jameel (2022 Global Conference on Wireless and Optical Technologies (GCWOT), 2022)
The security of multimedia data such as audio, video, and images has become a vast research subject due to the fast progress of multimedia technologies. The proposed study aims to develop a novel chaotic logistic map-based image encryption technique for multidimensional color images. Preprocessing is conducted initially in the proposed technique by down sampling the plaintext image. Instead of encrypting the whole color picture after preprocessing, encrypt each component independently (R, G, and B). To add extra unpredictability to the cipher text image, several chaotic mathematical equations are applied. To demonstrate the strength of the suggested work, certain statistical analysis and experimental results are performed, revealing that the new method outperforms the current ones.